Chronic hepatitis E virus infection in a patient with leukemia and elevated transaminases: a case report - Gauss, Annika; Flechtenmacher, Christa; Navid, Mojdeh Heidary; Eisenbach, Christoph; Stremmel, Wolfgang; Schnitzler, Paul (Journal of medical case reports, 2012)
Acute hepatitis E virus infection may cause mild, self-limiting hepatitis, either as epidemic outbreaks or sporadic cases, the latter of which have been reported in industrialized countries. Chronic infections are uncommon and have been reported in immunosuppressed patients, patients with human immunodeficiency virus infection, and patients with hematological malignancies.